Intestinal obstruction and mesenteric ischemia due to small intestine volvulus secondary to tumor of the root of the mesentery: case report - Fonseca, Jose V.; Rosales, Hugo F.; Arroyo, Aldo J.; Angulo, Paola C.; Castillo, Patricio A.; Blanco, Yurvis M.; Ruilova, Juan C.; Valdivieso, Patricia J. (International Journal of Research in Medical Sciences, 2024)
Neoplasms of the mesentery, although rare, can be benign and a low percentage malignant and derive from the mesenchyme, since the mesentery, which supports the jejunum and ileum along with its vessels, nerves and lymphatics, given its proximity to other structures, is a common site for primary and secondary neoplasms, as well as cysts. Symptoms are nonspecific and include abdominal pain, weight loss, and diarrhea. Computed tomography is the primary diagnostic tool, and other conditions such as infections can mimic neoplasms. Case report of a patient with a tumor of origin in the root of the mesentery that causes volvulation of the intestine due to its location and peritumoral adhesions, which leads to mesenteric ischemia of the compromised intestinal segment, and which required several surgical interventions ending with a syndrome of short intestine carrying a terminal jejunostomy. Mesenteric tumors have various clinical characteristics and can be primary or secondary. Early diagnosis with computed tomography is crucial to differentiate them. Although cystic tumors are usually benign, they can become complicated. Surgical treatment is necessary in most cases, and early detection improves results.